1995
DOI: 10.1016/s0266-7681(05)80160-3
|View full text |Cite
|
Sign up to set email alerts
|

Hand Ischaemia Following Radial Artery Cannulation

Abstract: Digital ischaemia following radial arterial cannulation is uncommon. It is usually the result of thrombotic occlusion of a dominant radial artery. However, factors other than arterial thrombosis per se may operate in the critically ill patient to produce digital ischaemia. The following case presentation includes a review of possible mechanisms of digital ischaemia following radial artery cannulation and discusses the therapeutic options available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
33
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 5 publications
0
33
0
2
Order By: Relevance
“…Hand ischaemia may be caused by two events: (a) digital embolisation of radial artery thrombus [15,16] and (b) in situ thrombosis of collateral vessels [17], which is most likely induced by severe vasospasm. Both events may lead to irreversible digital ischaemia requiring amputation, even in a setting of macroscopically and microscopically normal radial, ulnar, and superficial palmar arteries [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hand ischaemia may be caused by two events: (a) digital embolisation of radial artery thrombus [15,16] and (b) in situ thrombosis of collateral vessels [17], which is most likely induced by severe vasospasm. Both events may lead to irreversible digital ischaemia requiring amputation, even in a setting of macroscopically and microscopically normal radial, ulnar, and superficial palmar arteries [16].…”
Section: Discussionmentioning
confidence: 99%
“…Thrombus aspiration at the catheter tip may restore arterial pulsation in approximately 60 % of patients with suspected thrombosis, and intraarterial verapamil, prilocaine, and phentolamine have been successful in reversing ischaemic symptoms [20,22]. Other options include low-molecular-weight dextran or low-dose heparin treatment [15,16]. Geschwind et al demonstrated angiographic flow restoration with 20 % residual thrombus leading to clinical improvement in 5 of 7 patients treated with intra-arterial urokinase for radial artery occlusion [23].…”
Section: Discussionmentioning
confidence: 99%
“…Thrombosis may arise due to a wide variety of causes including iatrogenic cannulation, emboli, atherosclerosis or blunt and penetrating trauma (4,5,9). Cannulation of the radial artery results in endothelial injury, thus, exposing subendothelial collagen leading to platelet adherence and subsequent thrombus formation (3).…”
mentioning
confidence: 99%
“…A well-documented cause of radial artery thrombosis occurs secondary to radial artery cannulation (2). One study has shown this to occur in up to 60% of cases (9), necessitating microvascular consultation.…”
mentioning
confidence: 99%
See 1 more Smart Citation